Komparasi Efektivitas Minyak Pinus dan Minyak Alpukat Sebagai Pengganti Xylene Dalam Proses Penjernihan (Clearing) Histologi - Kawer, Joy Miracle Tumigolung; Cheriananda , Yessica Stefanie; Tumansery, Margareth; Kamengon, Alessandro Stefano; Lusiana, Diana Intan Gabriella; Setyoningrum, Fransisca Probo (Lembaga Teewan Journal Solutions, 2026)
Xylene is a standard clearing agent in histological tissue processing; however, its use poses a toxicity risk to the health of laboratory staff, making it necessary to find safer natural alternatives, such as pine oil and avocado oil. This experimental laboratory study aimed to compare the effectiveness of pine oil and avocado oil as xylene substitutes in improving the quality of mouse liver histological preparations. A total of twenty-seven mouse liver tissue sections were divided into three treatment groups: a xylene control group, an avocado oil group, and a pine oil group. The sections were then stained using the hematoxylin-eosin method and evaluated using a scoring system that assessed nuclear chromatin integrity, cytoplasmic contrast, preservation of tissue architecture, and microtome section quality. The results showed that pine oil achieved the highest total score, with mechanical performance comparable to xylene and superior preservation of cellular structure, while avocado oil demonstrated good cytoplasmic contrast and nuclear integrity but had limitations in section quality due to its high viscosity. Xylene itself excelled in ease of sectioning but resulted in poor nuclear integrity and cytoplasmic contrast due to repeated use. This study concludes that pine oil is the most effective and environmentally friendly alternative clarifying agent, while avocado oil still requires further process optimization before it can be widely recommended.